Transport Transitions: Advancing Sustainable and Inclusive Mobility (Springer Nature, 2025)
​​This is an open access book. It gathers the proceedings of the 10th edition of Transport Research Arena (TRA 2024), held on 15-18 April, 2024, in Dublin, Ireland. Contributions cover a wide range of research findings, methodological aspects, technologies and policy issues that are currently reshaping the transport and mobility system in different parts of Europe. Bridging between academic research, industrial developments, and regulations, this book offers a comprehensive review of the state-of-the art in transportation, with a special emphasis on topics concerning digital transition in transport, and inclusive and sustainable mobility alike. This is the first volume of a 6-volume set.